Comparative analisys of situational efficency of women volleyball teams participating in the Grand Prix 2013 and premier league of Bosnia and Herzegovina - Kapidzic, A.; Softic, L.; Kojic-Duric, S.; Selimovic, A.; Sljivic, E. (Sport Science - International Scientific Journal of Kinesiology, 2014)
In this paper about volleyball as an dynamic and demanding game which shows abilities of a player and his technical, tactical and conditional preparedness. The statistical data shows individual results of setters in both, winner and loser team. Taking into account that the Bosnian Premier League for Women in Volleyball hasn`t results on the European scene, the work processes data of the players in Bosnia and Herzegovina aiming results that will have importance in modelling and constituting training process for setters